Myrislignan Exhibits Activities Against Toxoplasma gondii RH Strain by Triggering Mitochondrial Dysfunction - Zhang, Jili; Si, Hongfei; Li, Bing; Zhou, Xuzheng; Zhang, Jiyu (Frontiers in Microbiology, 2019)
Toxoplasma gondii is a widespread obligatory parasitic protozoon that infects nearly all warm-blooded animals and causes toxoplasmosis. However, the current treatments for toxoplasmosis are limited by severe side effects. Myrislignan is a natural product from Myristica fragrans Houtt with wide pharmacological activities. In the current study, we tested the anti-T. gondii activity of myrislignan both in vitro and in vivo and explored its potential mechanism of action. The cytotoxicity of myrislignan in African green monkey kidney (Vero) cells was assessed using Cell Counting Kit-8 (CCK-8) assays. The in vitro effects of myrislignan on T. gondii were determined by quantitative PCR and Giemsa staining. An in vivo murine model of T. gondii infection was used to determine the efficacy of myrislignan. The changes in tachyzoites after myrislignan exposure were examined by electron microscopy. The impact of myrislignan on mitochondrial function in tachyzoites was assessed by MitoTracker Red CMXRos staining and an ATP detection kit. In vitro, myrislignan inhibited T. gondii tachyzoite proliferation with a 50% effective concentration of 32.41 μg/mL, and reduced the invasion of cells by tachyzoites (14.63% and 1.92% invasion rates for control and 70 μg/mL myrislignan, respectively). Importantly, myrislignan had no significant cytotoxicity against Vero cells at concentrations less than 132 μg/mL. In addition, surface shrinkage and mitochondrial damage were observed in tachyzoites after myrislignan exposure. The reduced ΔΨm and ATP levels in tachyzoites treated with myrislignan further confirmed mitochondrial damage. In the in vivo murine model, myrislignan treatment significantly reduced the parasite burden in tissues compared to no treatment. In conclusion, myrislignan had potent anti-T. gondii activities both in vitro and in vivo, and these activities might involve interruption of mitochondrial function. These data suggest that myrislignan might be a useful compound for the treatment of toxoplasmosis.